Hungary : Ex Post Evaluation of Exceptional Access Under the 2008 Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2011)
The program was successful in strengthening the economy and stabilizing market conditions, although part of the fiscal achievements were reversed after the program lapsed. The 2008 Stand-By Arrangement (SBA) with Hungary successfully stabilized financial market conditions and strengthened the economy through sizable fiscal consolidation and important structural reforms, despite significant challenges. The program was a successful example of joint collaboration between the authorities, the EU, and the IMF, setting an important precedent for future joint programs. Much of the structural fiscal adjustment has since been reversed.